The Military Perpetrator: A Narrative Analysis of Sentencing Judgments on Sexual Violence Offenders at the International Criminal Tribunal for the Former Yugoslavia (ICTY) - Inger Skjelsbæk (Journal of Social and Political Psychology, 2015)
This article examines the ways in which principal perpetrators of sexual violence crimes are situated in an international criminal court. It is based on a narrative psychological analysis of the sentencing judgments of the International Criminal Tribunal for the former Yugoslavia (ICTY). Specifically, the article argues that at least three narratives can be distinguished within the relevant legal texts: those of the chivalrous, the opportunistic and the remorseful perpetrator, each with a distinct plot structure: that of being a normal person responding adequately to a situation that is seen as normal; an abnormal person responding to what is seen as an abnormal (or extreme) situation; and a normal person responding inadequately to what is seen as an abnormal (or extreme) situation. The ways in which these plots come out depend on how the various voices in the courtroom position the perpetrator within the stories. Ultimately, these narratives represent different stories of how militarism and masculinity intersect to create different understandings of the soldier and military behavior. The mere analysis of this material, i.e. how sexual violence crimes are discussed in theatre in an international criminal court, is a scholarly contribution to the understanding of how sexual violence perpetrators can be situated in a war setting, and after. The findings suggest new perspectives on military perpetrators and changes in what is considered normal and abnormal behavior in military settings.